Research on Generative Artificial Intelligence Management - Wang, Shuheng (International Journal of Computer Science and Information Technology, 2024)
As a new technology, generative artificial intelligence technology not only promotes technological change, but also brings many governance risks because of its unique technical logic. For example, the introduction of massive data sets in the training process of generative artificial intelligence has the risk of data infringement, and the reinforcement learning model based on human feedback may exacerbate the generation and dissemination of false information, thus bringing a series of risks. Although the current law of our country has formed a preliminary framework for the regulation of generative artificial intelligence, there are still difficulties. Based on the development status of generative AI, this paper briefly discusses the practical problems and challenges of generative AI governance, the current governance framework and policies, and the future governance measures